The roles of GpsB and DivIVA in Staphylococcus aureus growth and division - Sutton, Joshua A. F.; Cooke, Mark; Tinajero-Trejo, Mariana; Wacnik, Katarzyna; Salamaga, Bartłomiej; Portman-Ross, Callum; Lund, Victoria A.; Hobbs, Jamie K.; Foster, Simon J. (Frontiers in Microbiology, 2023)
The spheroid bacterium Staphylococcus aureus is often used as a model of morphogenesis due to its apparently simple cell cycle. S. aureus has many cell division proteins that are conserved across bacteria alluding to common functions. However, despite intensive study, we still do not know the roles of many of these components. Here, we have examined the functions of the paralogues DivIVA and GpsB in the S. aureus cell cycle. Cells lacking gpsB display a more spherical phenotype than the wild-type cells, which is associated with a decrease in peripheral cell wall peptidoglycan synthesis. This correlates with increased localization of penicillin-binding proteins at the developing septum, notably PBPs 2 and 3. Our results highlight the role of GpsB as an apparent regulator of cell morphogenesis in S. aureus.